Divergent genetic mechanisms underlie reversals to radial floral symmetry from diverse zygomorphic flowered ancestors - Zhang, Wenheng; Steinmann, Victor W.; Nikolov, Lachezar; Kramer, Elena M.; Davis, Charles (Frontiers in Plant Science, 2013)
Malpighiaceae possess flowers with a unique bilateral symmetry (zygomorphy), which is a hypothesized adaptation associated with specialization on neotropical oil bee pollinators. Gene expression of two representatives of the CYC2 lineage of floral symmetry TCP genes, CYC2A and CYC2B, demarcate the adaxial (dorsal) region of the flower in the characteristic zygomorphic flowers of most Malpighiaceae. Several clades within the family, however, have independently lost their specialized oil bee pollinators and reverted to radial flowers (actinomorphy) like their ancestors. Here, we investigate CYC2 expression associated with four independent reversals to actinomorphy. We demonstrate that these reversals are always associated with alteration of the highly conserved CYC2 expression pattern observed in most New World Malpighiaceae. In New World Lasiocarpus and Old World Microsteria, the expression of CYC2-like genes has expanded to include the ventral region of the corolla. Thus, the pattern of gene expression in these species has become radialized, which is comparable to what has been reported in the radial flowered legume clade Cadia. In striking contrast, in New World Psychopterys and Old World Sphedamnocarpus, CYC2-like expression is entirely absent or at barely detectable levels. This is more similar to the pattern of CYC2 expression observed in radial flowered Arabidopsis. These results collectively indicate that, regardless of geographic distribution, reversals to similar floral phenotypes in this large tropical angiosperm clade have evolved via different genetic changes from an otherwise highly conserved developmental program.